A highly sensitive piezoresistive sensor with interlocked graphene microarrays for meticulous monitoring of human motions. Issue 33 (22nd July 2020) - Cheng, Lin; Qian, Wei; Wei, Lei; Zhang, Hengjie; Zhao, Tingyu; Li, Ming; Liu, Aiping; Wu, Huaping
Abstract : A flexible piezoresistive sensor based on interlocked graphene microarrays displays adjustable piezoresistance by changing the contact way of the graphene microarrays. Abstract : The development of flexible sensors with high sensitivity and a short response time has received great attention due to their potential applications in medical diagnosis and health monitoring. Herein, we demonstrate the design of a flexible piezoresistive sensor based on interlocked graphene microarrays on a flexible substrate. This sensor displays adjustable piezoresistance by changing the contact way of the graphene microarrays via micromanipulation, which endows the sensor with desirable compression sensitivity (10.41 kPa −1, <2.5 kPa), a fast response time (<19 ms), a broad measurement range (1.0 Pa–32 kPa) and excellent durability (>10 000 loading–unloading cycles). In particular, the fast-response characteristic of this sensor allows meticulous detection of complicated stimuli from various human motions by obviously changing the contact areas between the interlocked graphene microarrays when compared with a planar sensor with double-layered graphene films and a single microarray sensor, highlighting its potential application in wearable healthcare systems for more comprehensive and accurate analysis.